Familial Social Support and Psychological Well-being among Indonesian University Students: Dukungan Sosial Keluarga dan Kesejahteraan Psikologis di Kalangan Mahasiswa Indonesia - widiyastuti; Hardita, Kusumaningrum (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the relationship between familial social support and psychological well-being among students at the University of Muhammadiyah Sidoarjo. Despite the significance of social support in enhancing well-being, gaps persist in understanding its impact on university students. The aim is to address this gap by examining the correlation between family social support and psychological well-being among students. Using a quantitative research approach, data were collected from 263 active students through nonprobability sampling. Analysis involved Pearson product-moment correlation with SPSS 25. Findings revealed a significant positive correlation (p = 0.019), indicating that higher familial support enhances psychological well-being. The study also yielded an R-squared value of 0.021, suggesting that 2.1% of psychological well-being variance is attributed to social support. Most students exhibited moderate levels of familial social support (51.3%) and psychological well-being (61.6%). Implications include the importance of family support in promoting students' well-being, highlighting the need for interventions to strengthen familial bonds and support systems to enhance student mental health and academic performance. Highlight: Family support enhances student well-being, vital for academic success. Quantitative analysis confirms positive correlation between family support and well-being. Study recommends interventions to bolster familial bonds for student resilience. Kywoard: Familial social support, Psychological well-being, University students, Correlation analysis, Intervention implications.